International Legal Review of the Incident of Expulsion of Chinese Coast Guard Vessels in the North Natuna Sea - Moch. Rizal Fanani; Wahyu Prawesthi; Subekti Subekti; Nurhandayati Nurhandayati (Eduvest - Journal of Universal Studies, 2026)
The incident of the expulsion of a Chinese Coast Guard (CCG) vessel by Indonesian authorities in the North Natuna Sea has become a recurring phenomenon, raising complex questions about the legality of such actions under international maritime law. This study aims to analyze the legal status of CCG vessels in Indonesia's Exclusive Economic Zone (EEZ), the legality of expulsion actions, and the legal implications of China's Coast Guard Law 2021. Using normative legal research methods with a qualitative approach, this study examines UNCLOS 1982, arbitration awards, state practices, and international legal doctrines. The results of the study show that the right to freedom of navigation of CCG vessels in the EEZ is not absolute and is limited by the obligation to pay due regard to the sovereign rights of coastal states. The expulsion action carried out by Indonesia, as long as it is proportionate and non-escalatory, can be justified as a legitimate countermeasure to protect its sovereign rights from illegal intervention. Further, the study found that China's Coast Guard Law 2021 is fundamentally contrary to UNCLOS, seeks to replace international law with domestic legislation, and significantly increases the risk of conflict escalation in the region. The study concludes that while Indonesia's actions can be legally justified, the international maritime law framework now faces systemic challenges that threaten regional maritime stability.